PS8:159 Moving with the times: social media use amongst lupus patients. (21st March 2018) - Wheeler, LM; Pakozdi, A; Rajakariar, R; Lewis, M; Cove-Smith, A; Pyne, D
Abstract : Background: Over the last decade the rise in social media use has been almost exponential. There are numerous online platforms where patients can interact for support and information gathering. A study presented at the ACR in 2013 showed lupus patients were willing to participate in Facebook chats for the purposes of disease education. 1 We sought to discover current usage of social media amongst an ethnically mixed population attending an inner city tertiary lupus centre. Methods: Questionnaires were distributed to consecutive patients attending the Barts Lupus Centre from October 2016 to February 2017. 17 questions asked about patient demographics and patients use of online information and support services, particularly social media platforms, with regards to lupus. Results: 84 completed questionnaires were returned. 83% respondents were female. There were 28 South Asians, 26 Whites and 24 Blacks, 2 of other ethnic groups and 2 of mixed race. 64% (n=54) of patients accessed online lupus information and support sites. 45% percent (n=38) of patients reported using social media sites (26% South Asians, 34% Blacks and 34% Whites). Of those using social media 22% (n=8) patients used these tools daily and 30% (n=11) reported weekly use. Facebook (n=20), blogs (n=9), youtube (n=9), and Instagram (n=7) were cited as the most frequently used applications. Most patients (n=30) sought information on the disease, 17 (45%) wanted to find out about new treatments for lupus, 16 (42%) sought new ways to self-manage their disease, 14 (37%) sought interactions with other patients, and 10 (26%) were seeking support online. Patients most commonly wanted information on skin and joint complaints and family planning. 66% (n=56) thought their rheumatology team should have an online social media application to communicate with their patients. Conclusions: A significant proportion of our lupus patients (45%) use social media to access information and support for their disease. Facebook, blogs, Instagram and Youtube are commonly used. Social media applications can provide physicians with a tool to interact with lupus patients to improve accessibility to health care and better health outcomes. Reference: . Spring NH. 2013 ACR/ARHP Annual Meeting, abstract 990.